Harnessing community-led innovations: the role of participatory media in addressing gender-based violence. Issue 3 (3rd April 2018) - Thomas, Verena; Kauli, Jackie; Borrey, Anou
ABSTRACT: Gender-based violence (GBV) remains a key development challenge. In Papua New Guinea, a country with one of the highest rates of GBV, the issue has been prioritised in the national development agenda. The programme Yumi Kirapim Senis (Together Creating Change) was created to support the development of the National GBV Strategy. To build on existing understandings and workable solutions in communities, six community-led programmes were examined. This article explores a crucial component of the initiative which utilised participatory visual media to bridge communication gaps between national agencies and communities to drive social change at all levels.